2002
DOI: 10.1186/bcr454
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast cancer in Iran: a case-control study

Abstract: IntroductionGeographical variations in incidence and mortality rates of breast cancer suggest that the known risk factors for breast cancer may vary in different parts of the world and that environmental factors are of greater importance than genetic factors [1]. For instance, in Iran it has been shown that, even after adjusting for age, young women are at relatively higher risk for developing breast cancer than are their Western counterparts [2]. Thus, study of risk factors for breast cancer in Iranian women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
64
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 13 publications
15
64
3
Order By: Relevance
“…In this matched case control study, we confirmed the role of family history of breast cancer as risk factor for breast cancer among our women which is consistent with previous findings (Aghassi-Ippen et al, 2002;Ebrahimi et al, 2002;Norsa'adah et al, 2005;Hafize, 2011). However, younger age at diagnosis of the relative was not associated with increased risk of BC.…”
Section: Discussionsupporting
confidence: 92%
“…In this matched case control study, we confirmed the role of family history of breast cancer as risk factor for breast cancer among our women which is consistent with previous findings (Aghassi-Ippen et al, 2002;Ebrahimi et al, 2002;Norsa'adah et al, 2005;Hafize, 2011). However, younger age at diagnosis of the relative was not associated with increased risk of BC.…”
Section: Discussionsupporting
confidence: 92%
“…The pooled random effects estimate, comparing the risk of breast cancer amongst ever users of OCPs versus never users was 1.17 (95%CI 1.05-1.31) (Weir, 2007). The similar finding was observed in Iranian case-control study (Mandana Ebrahimi et al, 2002).…”
Section: Discussionsupporting
confidence: 77%
“…Lifetime duration of breast feeding less than 1 year has got increased risk of breast cancer as found from various studies (Gajalakshmi, 1991;2009;Rao, 1994;Mandana Ebrahimi et al, 2002). The pooled random effects estimate, comparing the risk of breast cancer amongst ever users of OCPs versus never users was 1.17 (95%CI 1.05-1.31) (Weir, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study done by Ebrahimi et al, found that never married women were at a higher risk for breast cancer. 27 Although marital status by itself is not a determining factor for increased or reduced breast cancer risk, but the main protective effect is from early first full-term pregnancy.…”
Section: Discussionmentioning
confidence: 99%